Analisis Kemampuan Bertanya Peserta Didik Pada Pembelajaran Tematik Tema 4 Subtema 1 Kelas IV Sekolah Dasar Negeri Maguwoharjo 1 Sleman, Yogyakarta - Aswatun Hasanah (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
In the process of learning one important part is to communicate with questions and answers. The inquiry in the learning process is a submission of questions both factual and opinion beginning with the guidance of teachers until the learners can understand and can be a habit. This research aims to describe the ability to ask learners with the theme of my works subtheme of the types of work of thematic learning subjects and to illustrate the constraints experienced by students of class IV elementary School of State of Maguwoharjo 1 Sleman Yogyakarta school year 2019/2020. The research method used in this study is a qualitative DESCRIPSITF approach. The result of this study is the ability of the students to be different because of lack of confidence, the fear is wrong and fear of being laughed at his friends who are still attached to the learners, and a stupid assumption when asked. These shortcomings can be eliminated in the following ways 1) the need for teacher creativity in delivering learning with strategies, methods, and the media and the approach used. 2) The courage and confidence of learners who need to be thrust and motivated by both teachers and parents. 3) Create active learning activities so that students are eager to learn. Keywords: Ability to ask, learners, thematic learning.